Effect of pretreatments and packaging on the growth of bacteria in value added summer onion products (Bangladesh Journal of Agricultural Research, 2016)
The experiment was carried out to investigate the bacteria in fresh and different processed onion. Total number of viable bacteria (cfu/g) in fresh onion and dehydrated processed onion packed in High Density Ployethylene (HDPE) and Aluminum foil (ALF) was estimated at 0, 6 and 12 month interval following storage at room temperature (RT, 20-250C) and refrigerated temperature (RFT, 50C). Samples tested were fresh onion (S0), dried onion (S1), blanched and dried (S2), blanched + sulphited and dried (S3), 25% salt osmosed and dried (S4), 60% sugar osmosed and dried (S5) and 55/15% sugar-salt osmosed dried onion (S6). It was found that the lowest bacterial count (2X101 and 9X101 cfu/g) was given by 25% salt osmosed onion (S4) and the total number of vialed bacteria (TVB) count in the other samples varied in the order of S3 S6 S5 S2 S1 (45-97x103 cfu/g) and sample S1 having no pretreatment before drying gave the highest TVB among the samples and the preservation effect was only due to reduction of aw during drying.Bangladesh J. Agril. Res. 41(3): 507-519, September 2016